Serum Neudesin Levels in Obese Adolescents - Aliye Çelikkol; Ciğdem Binay; Özge Ayçiçek; Savaş Güzel (Galenos Yayincilik, 2022)
INTRODUCTION: Advances in knowledge of neurotrophic factors are now revealing the complex control of energy homeostasis and appetite, as well as the crucial role these factors play in nervous system function. The aim of this study was to assess serum levels of neudesin in adolescents with obesity and to examine the relationship between these levels and metabolic outcomes. METHODS: Adolescents, aged 10-17 years were enrolled. Subjects were divided into normal weight, obese and morbidly obese subgroups. Serum neudesin concentrations were compared between the groups. RESULTS: In total, 88 adolescents were recruited, of whom 30 (34.1%) were normal weight, 15 (17.0%) were obese and 43 (48.9%) were morbidly obese. Neudesin levels were significantly lower in obese adolescents than in the control group (p=0.013). A correlation analysis applied to the whole study group revealed a negative correlation between serum neudesin concentration and body mass index (BMI) z scores (r=-0.40, p<0.001). Serum neudesin levels tended to increase in adolescents with metabolic syndrome, insulin resistance, dyslipidaemia, and hypertension but the differences were not significant (p=0.259, p=0.246, p=0.259, and p=0.523, respectively). DISCUSSION AND CONCLUSION: Serum neudesin levels were significantly correlated with BMI z score in obese adolescents. Generally, serum neudesin levels were low in obese and morbidly obese adolescents and tended to increase with the appearance of metabolic disorders. Both obesity and associated metabolic disorders have multifactorial causes. Therefore, we suggest that the role of the neudesin molecule in the regulatory mechanisms of obesity and metabolic disorders should be further investigated with well-designed studies enrolling larger groups.